2015
DOI: 10.1681/asn.2014010057
|View full text |Cite
|
Sign up to set email alerts
|

Human Urine-Derived Renal Progenitors for Personalized Modeling of Genetic Kidney Disorders

Abstract: The critical role of genetic and epigenetic factors in the pathogenesis of kidney disorders is gradually becoming clear, and the need for disease models that recapitulate human kidney disorders in a personalized manner is paramount. In this study, we describe a method to select and amplify renal progenitor cultures from the urine of patients with kidney disorders. Urine-derived human renal progenitors exhibited phenotype and functional properties identical to those purified from kidney tissue, including the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
88
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(94 citation statements)
references
References 42 publications
4
88
1
1
Order By: Relevance
“…[20][21][22][23][24] Numerous studies have reported the existence of a putative population of tubular progenitors in the adult human kidney, characterized by the co-expression of CD133 and CD24 surface markers. 26,[34][35][36][37][38][39][40][41] Putative tubular progenitor cells co-express tubular markers, and reside scattered among differentiated tubular cells within the tubule. [25][26][27] The choice of a tubule differentiation marker as the promoter, therefore, might not allow the existence of tubularcommitted progenitors to be excluded as they would be genetically tagged in a similar pattern to differentiated tubular cells.…”
Section: Markers Of Differentiated Tubular Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…[20][21][22][23][24] Numerous studies have reported the existence of a putative population of tubular progenitors in the adult human kidney, characterized by the co-expression of CD133 and CD24 surface markers. 26,[34][35][36][37][38][39][40][41] Putative tubular progenitor cells co-express tubular markers, and reside scattered among differentiated tubular cells within the tubule. [25][26][27] The choice of a tubule differentiation marker as the promoter, therefore, might not allow the existence of tubularcommitted progenitors to be excluded as they would be genetically tagged in a similar pattern to differentiated tubular cells.…”
Section: Markers Of Differentiated Tubular Cellsmentioning
confidence: 99%
“…[30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] The majority of these studies were performed in humans where lineage tracing cannot be performed; rather, stem cell identification and characterization relied on prospective isolation using specific markers followed by functional analyses, such as in vivo transplantation assays. [34][35][36][37][38][39][40][41] NCAM1 and ALDH1 (especially the ALDH1A2 paralogue) [42][43][44][45][46][47] have been suggested as stem and/or progenitor cell markers in the human foetal kidney and in Wilms' tumours during early nephrogenesis before nephron differentiation, and during mesenchymal-to-epithelial transition. [42][43][44][45][46][47] NCAM1 and ALDH1 allow the isolation and expansion of human nephron progenitor cells for the treatment of chronic kidney disease and are valuable therapeutic targets for Wilms' tumour eradication.…”
Section: Renal Progenitor Markersmentioning
confidence: 99%
“…What does this mean in regard to the study of Lazzeri et al 1 ? The authors use the markers glyCD133, CD24, and CD106 to identify and define RPCs.…”
Section: Search For Progenitor Cells In the Proximal Tubulementioning
confidence: 99%
“…In this issue, Lazzeri et al 1 explore the use of exfoliated cells in the urine of children affected by proteinuric kidney diseases for diagnostic and therapeutic purposes (from patient-to-dish-topatient). The authors investigate whether the isolated cells represent putative renal progenitor cells (RPCs) and test whether they are similar to a previously isolated putative progenitor population.…”
mentioning
confidence: 99%
See 1 more Smart Citation